2023
DOI: 10.1038/s41598-023-28672-3
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of rubber tips of artificial turf fields by goldfish

Abstract: Marine microplastics are one of the global environmental issues. The present study examined whether rubber tips of artificial sports fields could be marine microplastics. We observed the migration of rubber tips from the artificial turf field to the surrounding ditch connected to sewer pipes and then examined the ingestion of rubber tips using the goldfish Carassius auratus. The rubber tips found in sediments in the ditch suggest that the rubber tips could be sent to the river and released into the ocean. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The cyprinid Carassius auratus, the goldfish, is a commonly used fish model in ecotoxicity studies due to its wide availability and easy handling. Goldfish have been successfully used in both short-term (e.g., as short as 60 min) and long-term (e.g., nearly two months) exposure studies employing various endpoints (e.g., oxidative stress, LPO, behavioral changes, neurotoxicity, transcriptomic changes) [42][43][44][45][46][47][48]. In particular, C. auratus has shown significantly elevated MDA levels in the brain and liver (but not in the gills) after exposure to 0.5 mg L −1 of polyvinyl chloride (PVC) microplastic (0.1 to 1000 µm size) for 96 h [49].…”
Section: Introductionmentioning
confidence: 99%
“…The cyprinid Carassius auratus, the goldfish, is a commonly used fish model in ecotoxicity studies due to its wide availability and easy handling. Goldfish have been successfully used in both short-term (e.g., as short as 60 min) and long-term (e.g., nearly two months) exposure studies employing various endpoints (e.g., oxidative stress, LPO, behavioral changes, neurotoxicity, transcriptomic changes) [42][43][44][45][46][47][48]. In particular, C. auratus has shown significantly elevated MDA levels in the brain and liver (but not in the gills) after exposure to 0.5 mg L −1 of polyvinyl chloride (PVC) microplastic (0.1 to 1000 µm size) for 96 h [49].…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics are released from various sources such as litter, construction waste, agricultural plastic film, tires, fishing gear, and artificial turfs [1]. Previous studies have indicated artificial turf sports fields (ATSFs) to be an origin of MPs [17][18][19][20][21]. The artificial turf sports field consists of artificial turf fibers (ATFs, synthetic grass) and RTs used for the absorption of shocks generated due to player activities on the field.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous experiments have demonstrated that goldfish, Carassius auratus, Japanese crucian carp, Carassius auratus subsp. 2, and rainbow trout, Oncorhynchus mykiss, ingest RTs in the presence as well as absence of feed under laboratory conditions [20,21], suggesting that wild fishes can ingest RTs present in the aquatic environments. These results led us to consider that sports facilities could be one of the sources of MPs and we need to take measures to stop the migration of RTs from ATSFs to aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations